Factors affecting the utilization of cow dirt as a biogas energy source in Gogik Village, West Ungaran sub-district. Issue 3 (June 2021) - Heriyanti, A P; Budiyono,; Purnaweni, H; Dewi, N K; Khusniati, M
Abstract: The purpose of this study is to analyze the factors that influence the use of dairy cow dung as a source of biogas energy in Gogik Village, West Ungaran District. In this study, the method used is a qualitative method by conducting in-depth interviews, observation, and documentation. The results of this study indicate that the factors that influence the use of biogas energy sources can be viewed from technical factors, social factors, and economic factors. In terms of the availability of livestock and manure produced by Gogik Village, it is feasible to implement biogas technology on a household scale. In terms of livestock raising, Gogik Village has indeed met the eligibility requirements for the implementation of biogas. The community using biogas in Gogik Village has provided a land area according to the provisions of about 20 m 2 . In terms of social factors, the application of biogas technology in the community must be adjusted to the habits or culture of the community groups. On the other hand, the labor required to manage biogas in Gogik Village ranges from one to two people. In terms of economic factors, the effect of biogas use on community needs has not been fully felt by the biogas user community.